APLIKASI DESAIN HUNIAN SEMENTARA UNTUK KORBAN GEMPA DI KABUPATEN PASAMAN DAN PASAMAN BARAT - Yosritzal Yosritzal; Titi Kurniati; Hidayat Hidayat (LPPM Universitas Andalas, 2023)
A 6,1 Mw Earthquake hit West Sumatera on 22nd February 2022 at 08:39 Western Time of Indonesia. The epicenter of the earthquake was the slopes of Talamau Mountain. As a result, 27 people were recorded as dead and at least 457 people were injured. A total of 2,025 houses in West Pasaman Regency and 1,816 houses in Pasaman Regency were damaged. This resulted in at least 19,221 people being displaced. When the emergency response period ended, the refugees whose houses were damaged needed temporary housing until their houses were repaired. The purpose of the activities reported in this paper is to provide temporary housing for the victims, developed based on the standard designs from the PUPR Office. The temporary houses were made of wood, GRC and zinc with additional materials that can still be used from the rest of the building ruins. These activities were funded by the Indonesian Academics Association (ASASI), the Department of Civil Engineering of Andalas University, the Indonesian Red Crescent (BSMI) of West Sumatra, and Hatta University and hereinafter referred to as the Huntara Team. After the funds are raised, the next step is to conduct a survey to determine prospective recipients who deserve assistance. Based on the needs of prospective recipients and additional materials available, then modifications to the house design are made. Furthermore, the development of the house was carried out led by a local carpenter. The result of the activity is that five temporary houses have been built and used by the recipients.